Has economic freedom fostered bank performance? Panel evidence from China - Sufian, Fadzlan; Habibullah, Muzafar Shah (Routledge, 2010)
The impact of economic freedom on the well-being of the economy has been widely documented. Noticeably absent from the literature is empirical evidence on the impact of economic freedom on the banking sector. This article employs data on the Chinese banking sector and provides for the first time empirical evidence on the impact of economic freedom. We find evidence supporting far greater freedom for entrepreneurs to start businesses. The empirical findings seem to suggest that greater freedom of trade positively influences the performance of banks operating in the Chinese banking sector. However, the impact of the different dimensions of economic freedom is not uniform across Chinese banks with different ownership structures.